Arsenic-related oxidative stress in experimentally-dosed wild great tit nestlings. (April 2020) - Sánchez-Virosta, Pablo; Espín, Silvia; Ruiz, Sandra; Panda, Bineet; Ilmonen, Petteri; Schultz, Sandra L.; Karouna-Renier, Natalie; García-Fernández, Antonio J.; Eeva, Tapio
Abstract: Arsenic (As) is broadly distributed due to natural and anthropogenic sources, and it may cause adverse effects in birds. However, research on other elements (Pb, Hg and Cd) has been prioritized, resulting in scarce data on As exposure and related effects in wild birds. One of the mechanisms responsible for As toxicity is oxidative stress. Therefore, the aim of this study was to investigate if environmentally relevant As levels affected oxidative stress biomarkers in great tits ( Parus major ). This is the first field experiment studying the effects of As on oxidative stress in wild passerines. Wild great tit nestlings were orally dosed with sodium arsenite (Control: water, Low dose: 0.2 μg g −1 d −1 and High dose: 1 μg g −1 d −1 ; from day 3 to day 13 post-hatching). We intended to reach As concentrations similar to those at which passerines are exposed to at actual polluted areas. We compared the responses to the experimental manipulations (High, Low and Control groups) with those in an As/metal-exposed population breeding close to a Cu–Ni smelter in Finland (Smelter group). A set of antioxidants (tGSH, GSH:GSSG ratio, CAT, SOD, GST and GPx), and oxidative damage biomarkers (lipid peroxidation, protein carbonylation, 8-hydroxy-2′-deoxyguanosine formation in DNA, and telomere length) were explored in blood. Arsenic administration had no significant effect on most of the biomarkers measured: only the CAT activity was lower in the High As group and the GPx activity was enhanced in the Smelter group compared to the Control. Our results suggest that the dose and duration of the As exposure was not enough to induce oxidative damage in red cells of great tit nestlings. In spite of this, nestlings dosed with 1 μg g −1 d −1 of sodium arsenite showed non-significantly higher oxidative stress biomarkers than controls, suggesting that we were close to an effect level for the redox-defense system. Oxidative effects at equivalent As levels combined with other stressors cannot be dismissed. Graphical abstract: Image 1 Highlights: We evaluate the effects of As on biomarkers of oxidative stress in wild great tits. Arsenic administration had no significant effect on most of the biomarkers measured. Nestlings exposed to 1 μg g −1 d −1 of sodium arsenite showed lower CAT activity. Nestlings in the Smelter group had enhanced GPx activity. Abstract : Limited oxidative stress effects in the first field experiment dosing environmentally-relevant arsenic levels to wild great tit nestlings.